2021
DOI: 10.26434/chemrxiv-2021-b3fv1-v6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Atovaquone and Mebendazole as Repurposed Drugs with Antiviral Activity against SARS-CoV-2 (Version 5)

Abstract: Given the continuing heavy toll of the COVID-19 pandemic, therapeutic options for treatment are urgently needed. Here, we adopted a repositioning approach using in silico molecular modeling to screen FDA-approved drugs with established safety profiles for potential inhibitory effects against SARS-CoV-2. We used structure-based drug design to screen more than 2000 FDA approved drugs against SARS-CoV-2 main protease enzyme (Mpro) substrate-binding pocket. We additionally screened the top hits from both sites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…5 Mahmoud et al utilized molecular modeling to screen over 2,000 FDAapproved drugs, discovering that atovaquone, mebendazole, and ouabain exhibit high resistance to SARS-CoV-2. 6 Additionally, Xia et al's findings suggest that Melphalan may activate HMOX1, inhibit CDC20, and interact with MYC, aligning with prior empirical evidence. 7 These instances illustrate the high efficacy of computational methods like molecular docking and virtual screening in drug development, substantially reducing the scope of wet-lab experiments.…”
mentioning
confidence: 66%
“…5 Mahmoud et al utilized molecular modeling to screen over 2,000 FDAapproved drugs, discovering that atovaquone, mebendazole, and ouabain exhibit high resistance to SARS-CoV-2. 6 Additionally, Xia et al's findings suggest that Melphalan may activate HMOX1, inhibit CDC20, and interact with MYC, aligning with prior empirical evidence. 7 These instances illustrate the high efficacy of computational methods like molecular docking and virtual screening in drug development, substantially reducing the scope of wet-lab experiments.…”
mentioning
confidence: 66%
“…The antiviral effects of nucleoside analogues is believed to result from their incorporation specifically by viral polymerases leading to defects in viral replication or through their antimetabolite activity where they compete with cellular enzymes for their natural ligands [ 39 ]. We did not assess rosuvastatin in our in vitro screens of viral inhibition; however, in work by Ahmed et al, their structure-based drug repositioning approach for drugs with potential inhibitory effects on COVID-19 virus predicted anti-viral drugs and rosuvastatin among their top six hits and demonstrated the inhibitory effects on SARS-CoV-2 replication by rosuvastatin and other drugs in VeroE6 cells [ 44 ]. The physical properties of rosuvastatin, in particular its structural similarity to nucleoside analogues, may confer this statin with additional antiviral properties not had by the other statins that we assessed, and could explain why our EHR analysis found rosuvastatin as associated with a reduction in the relative risk of death in patients with COVID-19; whereas, NeMoCAD did not predict this drug.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Beck et al [6] employed computational methods to sift through extensive datasets, predicting that Azanavir, Remdesivir, and Kaletra could inhibit SARS-CoV-2. Mahmoud and colleagues [7] utilized computational molecular modeling to screen over 2000 FDA-approved drugs with established safety profiles and found that Atovaquone, Methylene Blue, and Valinomycin exhibited significant antiviral activities against SARS-CoV-2. Xia et al [8] conducted a case study on Melphalan (a key drug in anti-tumor therapy) using deep learning, revealing that Melphalan might activate HMOX1, inhibit CDC20, and interact with MYC, consistent with previous research findings.…”
Section: Introductionmentioning
confidence: 99%